MSME’s Marketing Performance Measures: Examining The Role Of Innovativeness & Competitive Strategy - Sulastini; Asmaji Darmawi (Universitas muhammadiyah malang, 2022)
MSME’s has a significant role towards the national economics of Indonesia. It offers the resilience on national economics, even when a crisis. Thus, that is important to ensure the marketing performance. This research aimed to measure the MSME’s marketing performance from the innovativeness and competitive strategy. The research involves 50 MSME’s in Banjarmasin. The data analysis to test the hypotheses are the multi regression analysis. The results indicates that all of the hypotheses is accepted. However, the innovativeness indicates more prevalent results than the competitive strategy. This is due to the nature of MSME’s is a rather have a collaboration than competing each other. This research contributes to the current literature by providing an evidence of presents MSME’s marketing performance from the innovativeness and competitive strategy.